Methods of Studying the Specific Relationships of Tradition and Non-Tradition in Music Education - Akbar Otaxonov (International Journal on Orange Technologies, 2021)
It is important to organize the learning process with the help of information and technical means. In particular, knowledge of the basic principles of non-traditional forms of music education and their essence has a positive impact on the effectiveness of music education. The topic covers the methodology of studying the specific relationships of tradition and non-tradition in music education.